Venous Oxygenation Measurements in the Upper Arm: Reproducibility and Sensitivity to a Physical Challenge - J. Diogo Fernandes; Koen P. A. Baas; Matthan W. A. Caan; Bart J. Biemond; John C. Wood; Aart J. Nederveen (Magnetic Resonance in Medicine, 2026)
ABSTRACT Purpose The feasibility and reproducibility of adapting the T2‐Relaxation‐Under‐Spin‐Tagging (TRUST) MRI sequence for noninvasive measurement of venous oxygenation in the upper arm were investigated, aiming to enable future in vivo validation of T 2 b ‐oxygenation calibration curves in sickle cell disease (SCD). Methods The TRUST sequence, originally developed for the brain, was optimized for the upper arm by comparing control, label and difference signal. Accuracy was assessed using a phantom experiment. Twelve healthy volunteers underwent repeated TRUST scans using two different protocols: Three‐averages and One‐average. Reproducibility and temporal resolution were investigated, and a handgrip exercise was used to assess sensitivity to physiological changes. Statistical analyses included coefficient of variation (CV), within‐subject CV (wsCV), and Bland–Altman analysis. Results Phantom experiments demonstrated accurate T 2 estimation at low expected velocities with deviations from reference less than 16 ms (11.2%). In vivo, the adapted sequence provided faster and reproducible T 2 b (86.0 ± 30.0 ms) and Y v measurements (66.1% ± 11.7%). Reducing the number of averages improved temporal resolution without compromising measurement reproducibility (bias: 16.3 to 7.6 ms, wsCV: 39.8% to 35.3%). During exercise, significant decreases in T 2 b and Y v were observed in both the superficial and deep vein: mean T 2 b decreased from 87.2 to 58.9 ms ( p < 0.001) in the cephalic vein, and from 93.3 to 71.3 ms ( p < 0.001) in the brachial vein. Conclusion The adapted TRUST protocol enables reproducible assessment of venous oxygenation in the upper arm, providing a technique for future validation and recalibration of T 2 b –oxygenation curves in SCD.